Apparent digestibility of fish waste oil in diets for laying hens - Brelaz , Kely Cristina Bastos Teixeira Ramos; Cruz , Frank George Guimarães; Rufino, João Paulo Ferreira; Brasil , Ronner Joaquim Mendonça; Silva, André Ferreira; Costa , Valcely Rocha; Santos , Adriene Núzia de Almeida (Acta Scientiarum. Animal Sciences, 2023)
This study aimed to assess the impact of incorporating fish waste oil into laying hens’ diets on apparent nutrient digestibility and apparent metabolizable energy. A total of 72 Hisex White laying hens (25 weeks old) were employed in a completely randomized design, with treatments consisting of a control diet and an experimental diet (containing 3.5% fish oil), each with six replicates of six birds. The collected data underwent polynomial regression analysis at a 5% significance level. No significant differences (p > 0.05) were observed in the digestibility of dry matter, crude protein, mineral matter, crude fiber, and non-nitrogenous extract between the reference diet and the experimental diet containing fish waste oil. However, there were significant differences (p < 0.05) in the digestibility of ethereal extract (fat). Despite this, values for apparent metabolizable energy and apparent metabolizable energy corrected by nitrogen balance did not exhibit significant differences (p > 0.05) between the reference and experimental diets. In conclusion, the incorporation of 3.5% fish waste oil in laying hens’ diets led to satisfactory nutrient digestibility and enhanced fat digestibility. Importantly, this inclusion did not adversely impact energy metabolism.